Improvement of the LbCas12a-crRNA System for Efficient Gene Targeting in Tomato - Vu, Tien Van; Doan, Duong Thi Hai; Tran, Mil Thi; Sung, Yeon Woo; Song, Young Jong; Kim, Jae-Yean (Frontiers in Plant Science, 2021)
Plant gene targeting (GT) can be utilized to precisely replace up to several kilobases of a plant genome. Recent studies using the powerful clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated (Cas) nucleases significantly improved plant GT efficiency. However, GT for loci without associated selection markers is still inefficient. We previously utilized Lachnospiraceae bacterium Cas12a (LbCas12a) in combination with a replicon for tomato GT and obtained high GT efficiency with some selection markers. In this study, we advance our GT system by inhibiting the cNHEJ pathway with small chemical molecules such as NU7441. Further optimization of the GT is also possible with the treatment of silver nitrate possibly via its pronounced actions in ethylene inhibition and polyamine production. Importantly, the GT efficiency is significantly enhanced with the use of a temperature-tolerant LbCas12a (ttLbCas12a) that is capable of performing target cleavage even at low temperatures. Targeted deep sequencing, as well as conventional methods, are used for the assessment of the editing efficiency at both cell and plant levels. Our work demonstrates the significance of the selection of gene scissors, the appropriate design and number of LbCas12a crRNAs, the use of chemical treatments, and the establishment of favorable experimental conditions for further enhancement of plant HDR to enable efficient GT in tomato.